On the Resource Allocation of Hierarchical NOMA for Fog-RAN with Energy Harvesting - Papanikolaou, Vasilis K.; Mitsiou, Nikos A.; Diamantoulakis, Panagiotis D.; Goudos, Sotirios K.; Karagiannidis, George K. (2021 10th International Conference on Modern Circuits and Systems Technologies, MOCAST 2021, 2021)
In this paper, we introduce a multiple access protocol, termed hierarchical non-orthogonal multiple access (HiNOMA), optimized for fog-radio access networks (F-RANs). Resource allocation optimization is deemed critical in order to guarantee the users' fairness in the network, while energy efficiency can be increased through energy harvesting (EH) at the user equipment (UE) nodes. Therefore, the HiNOMA protocol with energy harvesting capabilities is examined for F-RANs, leading to the optimization of the proportional fairness metric. Finally, numerical results reveal the effectiveness of the joint design and the interesting trade-off between harvested power and achievable rate in the case of F-RAN.
Created from Fastlane, Scopus look-up
Keywords: convex optimization; energy harvesting; hierarchical noma; non-orthogonal multiple access (noma); resource allocation